MANAJEMEN PEMBIAYAAN SEKOLAH DASAR BERBASIS ISLAM STUDY KASUS DI SD UMMU AIMAN LAWANG - Deden Ramdhani; Muhammad Ubaidillah (Jurnal Inovatif Manajemen Pendidikan Islam, 2022)
In the implementation of education, financing is a potential that greatly determines the quality of human resources and is an inseparable part of education administration management. Because cost is very important in the implementation of education, so universities need effective and efficient financing management, in order to produce quality graduates. In improving the quality of graduates, strong support is needed in learning activities, the use of educational facilities and infrastructure in accordance with the provisions of national education standards. Of the many criteria for improving the quality of graduates, it is inseparable from the costs in the implementation of the educational process. This study aims to describe and find out: (1) Budget planning to improve the quality of education at Ummu Aiman Lawang Elementary School and Islamic Elementary School (2) Budget fulfillment strategy to improve the quality of education at Ummu Aiman Lawang Elementary School and Islamic Elementary School (3) Budget evaluation to improve the quality of education at Ummu Aiman Lawang Elementary School. This research uses a qualitative approach of analytical descriptive type. The methods of data collection are observation, interviews and documentation. The data analysis technique uses Miles and Huberman's interactive analysis model which includes four components, namely data collection, data reduction, data presentation and conclusion drawing. Checking the validity of data using Credibility, Transferability, Dependability, and Confirmability. The results showed that: 1) the planning of the education budget of SD Ummu Aiman Lawang was prepared and outlined in the form of an RKAS held at the end of each year by determining all programs along with the budget of each program. Involving school stakholders, through meetings and meeting decisions that have been agreed upon again decided by the head of the foundation 2) Strategies for fulfilling the budget to improve the quality of education at Ummu Aiman Lawang Elementary School and namely: a. independent work unit strategy, b. donations of funds from foundations and students, c. having links with foreign countries, and d. submitting proposals to the government. 3) Evaluation of Education Financing in Improving Quality. Education at SD Ummu Aiman Lawang is carried out through: 1) program evaluation is carried out every semester or year, 2) evaluation of employee performance results, 3) evaluation of organizational mechanisms, 4) evaluation of internal and external analysis results.